The Impact Of Digital Transformation On The Creative Economy: Opportunities And Challenges For Small And Medium Enterprises - Muzakkir, Muzakkir; Ahmad, Ahmad; Naim, Yanto; Yusri, Yusri (Jurnal Ekonomi, 2024)
This article examines the impact of digital transformation on the creative economy, focusing specifically on opportunities and challenges faced by small and medium enterprises (SMEs). As digital technology increasingly permeates all business domains, the creative economy sector—often driven by innovation and adaptability—presents a unique context for understanding the implications of this shift. Utilizing a qualitative approach, this study employs library research to explore key literature, examining existing frameworks, theories, and case studies that highlight the role of digital tools in reshaping business processes, market access, and consumer engagement for SMEs. Findings indicate that digital transformation offers substantial opportunities for SMEs, including expanded market reach, enhanced brand visibility, and streamlined operational efficiencies. However, these potential benefits are often offset by challenges such as limited access to digital infrastructure, skill gaps, and financial constraints, which can impede SMEs' adaptability and long-term competitiveness. This research emphasizes the need for targeted policy interventions, capacity-building programs, and collaborative strategies to help SMEs navigate digital transformation effectively. The findings contribute to the broader discourse on the evolving creative economy, offering insights for policymakers, industry stakeholders, and SMEs seeking to leverage digital tools to enhance their competitiveness and resilience.